PENGARUH 'URF DALAM HUKUM PEMINANGAN DAN AKAD NIKAH, STUDI KOMPARASI KHI DI INDONESIA DENGAN QĀNŪN AL-AHWĀL AL-SHAKHṢIYYAH DI YAMAN - Abidin, Muhammad Zainal; Zaman, Ahmad Zuhairus (Mabahits : Jurnal Hukum Keluarga Islam, 2024)
One of the sources of Islamic law is the 'urf argument. The use of this argument is often found in cases where there are no provisions in the Qur'an or hadith. This paper examines the role of 'urf in the articles of the Compilation of Islamic Law in Indonesia and the Personal Status Law in Yemen, particularly in the articles related to the law of engagement and marriage contracts. This research is a qualitative study with a literature review type. (library research). Using a legislative approach and also a comparative approach with a Micro Comparison scale. The main sources used are the KHI book and the Qānūn al-Aḥwāl al-Shakhṣiyyah al-Yamani, which were then analyzed qualitatively to determine the extent of the role of 'urf in those articles. The conclusion of this research is: 1. The importance of considering 'urf in marriage law legislation, taking into account Islamic legislation which is largely absorbed from fiqh schools with different societal 'urf settings. 2. In the context of marriage proposal and marriage contract law, the application of 'urf in the Qānūn al-Aḥwāl al-Shakhṣiyyah of Yemen receives more emphasis than the KHI of Indonesia. Proven by the recitation of Surah Al-Fatiha and the exchange of gifts in Article (2), and the mention of the formula of offer and acceptance using phrases that mean "marriage" according to 'urf in the text of the Article. (7). Also, the Personal Status Law of Yemen opens the possibility of marriage contracts via letter, telephone, or video conference. Meanwhile, the KHI places more emphasis on the use of delegation to avoid the process of remote marriage contracts.